THEORY, REALITY AND PERCEPTION OF CSR: COMPARATIVE STUDY BETWEEN INDIA AND THE SLOVAK REPUBLIC - Peter Bielik; Elena Horsk; Andrea Ubreziova (Universitas Gunadarma, 2012)
During last decades global society has witnessed remarkable growth of global issues, both on social and environmental level, that have resulted in broad changes in the global economy. These aspects have increased the neccesity for more systematic and sustainable approach towards the way business is done on local and global level. Therefore, corporate social responsiblity (CSR) has become an effective tool, many companies have decided to apply within domestic as well as international environment. The main goal of this paper is therefore to describe CSR policy and strategies of McDonald’s – worldwide fast food chain leader. Moreover, we analyze reasons of different perception of McDonald’s CSR strategies between Indian and Slovak consumers. CSR has become an important instrument to develop and implement more responsible business strategies that contributes not only to development of companies’ themselves, but towards development of society and environment as well. Although, we can find difference in approach towards CSR implementation in business strategies and the strenght of their impact on society and environment. Significant role in the strenght and kinds of influence CSR has, plays the context in which companies are motivated to support and develop CSR strategies and the type of innitiative. Various approaches (including motives and innitiatives) can results in different perceptions of company’s CSR strategies and attempts as we will see in presented case comparative study. Key words: consumer, corporate social responsibility (CSR), global environment, local business, perception, sustainable business